Assessment of sodium chloride tolerance and antibiotic resistance of Citrobacter braakii EC-PS1 and Macrococcus caseolyticus Li-PT1 isolated from artisanal cheeses - György É.; Laslo É.; Unguran K. A. (Acta Universitatis Sapientiae: Alimentaria, 2022)
The different varieties of cheese are fermented dairy products with high nutritional value, which have been part of the healthy human diet for centuries. Cheeses are characterized by complex and diverse microbiota carrying beneficial, spoilage, or foodborne pathogen bacteria. Harmful bacteria originate from the production chain. Identification and characterization of microorganisms in cheese are important nutritional, food safety, and technological issues. During this study, Citrobacter braakii EC-PS1 and Macrococcus caseolyticus Li-PT1 bacteria strains, isolated on selective mediums from two artisanal cheeses, were identified by way of 16S rDNA gene sequence analysis. Their antibiotic resistance and NaCl stress tolerance were also determined M. caseolyticus Li-PT1 showed tolerance to 6.5% and 10% NaCl. The increasing NaCl concentration above 15% contributed to the decrease of viability in bacteria. The increasing NaCl concentration to 10% contributed to the decrease of viability in C. braakii EC-PS1 bacteria. The identified bacterial species exhibited different levels of resistance to the tested antibiotics C. braakii EC-PS1 showed resistance to chloramphenicol, ampicillin, and streptomycin, whereas M. caseolyticus Li-PT1 was susceptible only to two antibiotics (erythromycin, tetracycline) out of the eight tested.